2016
DOI: 10.1021/jacs.6b08467
|View full text |Cite
|
Sign up to set email alerts
|

Long Coherence Times in Nuclear Spin-Free Vanadyl Qubits

Abstract: Quantum information processing (QIP) offers the potential to create new frontiers in fields ranging from quantum biology to cryptography. Two key figures of merit for electronic spin qubits, the smallest units of QIP, are the coherence time (T), the lifetime of the qubit, and the spin-lattice relaxation time (T), the thermally defined upper limit of T. To achieve QIP, processable qubits with long coherence times are required. Recent studies on (PhP-d)[V(CS)], a vanadium-based qubit, demonstrate that millisecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
173
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(182 citation statements)
references
References 64 publications
8
173
1
Order By: Relevance
“…As the first step in that direction, we have studied the magnetic properties of V-Ln heterometallic complexes. It has been found that the T m values in complexes of vanadium(IV) with diamagnetic lanthanides are generally comparable to those exhibited by other vanadium-based qubits specially designed for this purpose [3][4][5][6][7][8][9]15]. First of all, this owes to the nuclear spin-free first coordination sphere of the VO 6 moiety.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…As the first step in that direction, we have studied the magnetic properties of V-Ln heterometallic complexes. It has been found that the T m values in complexes of vanadium(IV) with diamagnetic lanthanides are generally comparable to those exhibited by other vanadium-based qubits specially designed for this purpose [3][4][5][6][7][8][9]15]. First of all, this owes to the nuclear spin-free first coordination sphere of the VO 6 moiety.…”
Section: Discussionmentioning
confidence: 56%
“…We dissolved two representative compounds (I and III) in glass-forming water/glycerol mixture (~50/50% v/v) and recorded two-pulse echo-detected (ED) EPR spectra in such frozen (glassy) solutions ( Figure 5). Note that mostly vanadium-based candidates for spin qubits were investigated in the solid crystalline state; however, a few earlier works used dissolution as well [3,4,7,13,14]. In particular, this approach allowed obtaining very long decoherence times at low temperatures, especially in nuclear spin-free solvents.…”
Section: Relaxation Properties Of Complexes In Frozen Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for such a system to be a plausible double qubit, the coherence time of each qubit must be large enough to be able to perform quantum operations. Some molecular complexes have promising coherence times to be considered as possible candidates for qubits, but no measurements have been carried out on nickel complexes yet. Such studies were beyond the scope of the work reported in this paper; we have focused on the design of Ni II binuclear complexes and the analysis of their magnetic anisotropy and exchange coupling with a view to developing potential candidates for use as qubits.…”
Section: Introductionmentioning
confidence: 99%